Effects of FGF2/FGFR1 Pathway on Expression of A1 Astrocytes After Infrasound Exposure - Zou, Lin-Hui; Shi, Ya-Jun; He, Hua; Jiang, Shi-Mei; Huo, Fang-Fang; Wang, Xiao-Mu; Wu, Fan; Ma, Lei (Frontiers in Neuroscience, 2019)
Two types of reactive astrocytes, A1 and A2 astrocytes, are induced following neuroinflammation and ischemia. In this study, we evaluated the effects of the fibroblast growth factor (FGF)2/FGF receptor (FGFR)1 pathway on A1 and A2 astrocytes in the rat hippocampus using double-labeling immunoﬂuorescence following infrasound exposure. A1 astrocytes were induced in the CA1 region of the hippocampus after exposure to infrasound for 3 days. The number of microglial cells was also increased, and we investigated if these might be responsible for the reactivity of A1 astrocytes. Accordingly, expression levels of C3 and Iba-1, as markers of A1 astrocytes and microglial cells respectively, were both up-regulated in rat hippocampus following infrasound exposure, as demonstrated by western blot. We also explored the effect of the FGF2/FGFR1 pathway on A1 astrocyte reactivity by pretreating rats with FGF2 or the specific FGFR1 antagonist, PD173074. A1 astrocytes were gradually down-regulated by activation of the FGF2/FGFR1 pathway and were up-regulated by inhibition of the FGF2/FGFR1 pathway after infrasound damage. These results further our understanding of the role of reactive astrocytes in infrasound-induced central nervous system injury and will thus facilitate the development of new treatments for these injuries.